The Relationship Knowledge and Family Support With Pregnant Women's Class Participation - Liya Lugita Sari; Taufianie Rosita; Yesi Putri (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Knowledge is a motivating factor for someone to change their behavior. If a pregnant woman knows about a class for pregnant women, it is likely that they will take the class. Family support is also very influential in determining a mother's health behavior. Pregnant women follow the advice given by their families. This study aims to identify the relationship between family knowledge and family support and the involvement of pregnant women in classes in the work area of the Manna City Health Center, South Bengkulu Regency. Analytical use as a cross-sectional research design This research involved 45 samples from all pregnant women in their third trimester in the Manna City Health Center work area, South Bengkulu Regency, from October to November 2022. Data analysis used univariate and bivariate analysis and the chi-square test. The results obtained were mostly with insufficient knowledge (42.2%), with families who were not supportive (62.2%) and who did not regularly attend classes for pregnant women (51.1%). The results of the chi-square test for the knowledge variable show that the calculated ?2 value (6.72) > ?2 table (5.491) and the value ?(0.035) <?(0.05), and for the family support variable, the calculated ?2 value (6.63) > ?2 table (3.481) is obtained. and the value ?(0.010)<?(0.05). This research concludes that there is a relationship between knowledge, family support, and class participation for pregnant women. It is recommended that midwives be more active in disseminating information about the pregnant mother class program to pregnant women and to husbands, partners, and families.